Cytotoxicity of glass ionomer cements containing silver nanoparticles - Siqueira, Patrícia-Correia; Magalhães, Ana-Paula-Rodrigues; Pires, Wanessa-Carvalho; Pereira, Flávia-Castro; Silveira-Lacerda, Elisângela-Paula; Carrião, Marcus-Santos; Bakuzis, Andris-Figueiroa; Souza-Costa, Carlos-Alberto [UNESP]; Lopes, Lawrence-Gonzaga; Estrela, Carlos (My University, 2015)
Background: Some studies have investigated the possibility of incorporating silver nanoparticles (NAg) into dental materials to improve their antibacterial properties. However, the potential toxic effect of this material on pulp cells should be investigated in order to avoid additional damage to the pulp tissue. This study evaluated the cytotoxicity of conventional and resin-modified glass ionomer cements (GIC) with and without addition of NAg. Material and Methods: NAg were added to the materials at two different concentrations by weight: 0.1% and 0.2%. Specimens with standardized dimensions were prepared, immersed in 400 μL of culture medium and incubated at 37°C and 5% CO2 for 48 h to prepare GIC liquid extracts, which were then incubated in contact with cells for 48 h. Culture medium and 0.78% NAg solution were used as negative and positive controls, respectively. Cell viability was determined by MTT and Trypan Blue assays. ANOVA and the Tukey test (α=0.05) were used for statistical analyses. Results: Both tests revealed a significant decrease in cell viability in all groups of resin modified cements (p < 0.001). There were no statistically significant differences between groups with and without NAg (p < 0.05). The differences in cell viability between any group of conventional GIC and the negative control were not statistically significant (p > 0.05). Conclusions: NAg did not affect the cytotoxicity of the GIC under evaluation.
Keywords: Cell culture techniques; Glass ionomer cements; Metal nanoparticles; Nanotechnology; Totoxicity